2020
DOI: 10.1111/nph.16385
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning the soil microbiome through plant–soil feedbacks suppresses an aboveground insect pest

Abstract: Summary Soils and their microbiomes are now recognized as key components of plant health, but how to steer those microbiomes to obtain their beneficial functions is still unknown. Here, we assess whether plant–soil feedbacks can be applied in a crop system to shape soil microbiomes that suppress herbivorous insects in above‐ground tissues. We used four grass and four forb species to condition living soil. Then we inoculated those soil microbiomes into sterilized soil and grew chrysanthemum as a focal plant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 59 publications
4
71
4
3
Order By: Relevance
“…Hence we cannot proof wich microbes present in the inoculum entered the plant. In an earlier study (Pineda et al 2020) we compared the bacterial and fungal community of soil inocula (conditioned by different species of grasses and forbs) and of sterilized soil. In that study, soil inocula have much higher bacterial and fungal richness than the sterilized soil as expected, and several bacterial phyla (Acidobacteria, Traumarcheota, Armatimonadetes, Atribacteria, BRC1, Candidatus_Berkelbacteria, Chlamydiae, Elusimicrobia, FBP, FCPU426, Fibrobacteres, Gemmatimonadetes, Hydrogenedentes, Nitrospirae, Parcubacteria, Verrucomicrobia, TM6) and a fungal phylum (Mucoromycota) were enriched in soil inocula.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence we cannot proof wich microbes present in the inoculum entered the plant. In an earlier study (Pineda et al 2020) we compared the bacterial and fungal community of soil inocula (conditioned by different species of grasses and forbs) and of sterilized soil. In that study, soil inocula have much higher bacterial and fungal richness than the sterilized soil as expected, and several bacterial phyla (Acidobacteria, Traumarcheota, Armatimonadetes, Atribacteria, BRC1, Candidatus_Berkelbacteria, Chlamydiae, Elusimicrobia, FBP, FCPU426, Fibrobacteres, Gemmatimonadetes, Hydrogenedentes, Nitrospirae, Parcubacteria, Verrucomicrobia, TM6) and a fungal phylum (Mucoromycota) were enriched in soil inocula.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we observed that soil inoculation led to a reduction in thrips damage in chrysanthemum (Pineda et al 2020). Here, our objective was to examine the interactive effects of inoculation and thrips damage.…”
Section: Phase 2: Test Phasementioning
confidence: 99%
See 3 more Smart Citations